Analysis of Radiation Dose to the Shoulder by Treatment Technique and Correlation With Patient Reported Outcomes in Patients Receiving Regional Nodal Irradiation - Bazan, Jose G.; DiCostanzo, Dominic; Hock, Karen; Jhawar, Sachin; Kuhn, Karla; Lindsey, Kylee; Tedrick, Kayla; Healy, Erin; Beyer, Sasha; White, Julia R. (Frontiers in Oncology, 2021)
BACKGROUND/PURPOSE: Shoulder/arm morbidity is a late complication of breast cancer treatment with surgery and regional nodal irradiation (RNI). We set to analyze the impact of radiation technique (intensity modulated radiation therapy [IMRT] or 3D conformal radiation therapy [3DCRT]) on radiation dose to the shoulder with a hypothesis that IMRT use results in smaller volume of shoulder receiving radiation. We explored the relationship of treatment technique on long-term patient-reported outcomes using the quick Disabilities of the Arm, Shoulder, and Hand (q-DASH) questionnaire. MATERIALS/METHODS: We identified patients treated with adjuvant RNI (50 Gy/25 fractions) from 2013-2018. We retrospectively contoured the shoulder organ-at-risk (OAR) from 2 cm above the ipsilateral supraclavicular (SCL) planning target volume (PTV) to the inferior SCL PTV slice and calculated the absolute volume of shoulder OAR receiving 5-50 Gy (V5-V50). We identified patients that completed a q-DASH questionnaire ≥6 months from the end of RNI. RESULTS: We included 410 RNI patients: 54% stage III, 72% mastectomy, 35% treated with IMRT. IMRT resulted in significant reductions in the shoulder OAR volume receiving 20-50 Gy vs. 3DCRT. In total, 82 patients completed the q-DASH. The mean (SD) q-DASH=25.4 (19.1) and tended to be lower with IMRT vs. 3DCRT: 19.6 (16.4) vs. 27.8 (19.8), p=0.078. CONCLUSION: We found that IMRT reduces radiation dose to the shoulder and is associated with a trend towards reduced q-DASH scores ≥6 months post-RNI in a subset of our cohort. These results support prospective evaluation of IMRT as a technique to reduce shoulder morbidity in breast cancer patients receiving RNI.